Identifikasi Tampilan Visual Pada Arsitektur Vernakular di Rejang Lebong dan Lebong - Fadhilah Widya Dhana; Debby Seftyarizki; Panji Anom Ramawangsa (EduInovasi: Journal of Basic Educational Studies, 2024)
The Rejang tribe is one of the tribes that has long inhabited areas in the Bengkulu Province and has spread across several regencies in the province. There are differences between the Rejang tribe in Lebong Regency and the Rejang tribe in Rejang Lebong Regency due to adaptation and cultural blending. This study identifies the differences in form characteristics in Rejang vernacular architecture in Lebong and Rejang Lebong Regencies, including roof shape, wall board arrangement, window types, door types, building materials, building colors, room dimensions, building orientation, and building foundations. Three samples of vernacular buildings from each region will be analyzed using the Descriptive Qualitative method based on non-numeric data. The results show that there are 5 differences and only 4 similarities in the physical characteristics of vernacular architecture in Lebong and Rejang Lebong Regencies.